2023
DOI: 10.1097/j.jcrs.0000000000001135
|View full text |Cite
|
Sign up to set email alerts
|

SS-OCT–based ocular biometry in an adult Korean population with cataract

Abstract: Design: Retrospective case series. Methods: Ocular biometric values of 5273 eyes of 5273 Korean patients undergoing cataract surgery measured with the IOLMaster 700 at the Seoul National University Hospital between November 2019 and December 2021 were reviewed.Results: A total of 5273 eyes of 5273 Korean patients were analyzed. The mean ± SD age was 66.1 ± 12.8 years, and 62% were female. Overall, age and ocular biometric parameters were correlated with each other. Particularly, age showed a negative correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Han patients had deeper ACD than Uyghur patients, and male patients in all ethnic groups had deeper ACD than female patients. The results were consistent with the sex differences between the correlation of ACD and AL in patients with cataracts in South Korea and Israel [12,34] . It is suggested that female patients with a shallow ACD may be more likely to develop acute primary angle-closure glaucoma than male patients based on cataract impacts.…”
Section: Ocular Biometric Characteristics Of Ethnic Groupssupporting
confidence: 87%
See 1 more Smart Citation
“…Han patients had deeper ACD than Uyghur patients, and male patients in all ethnic groups had deeper ACD than female patients. The results were consistent with the sex differences between the correlation of ACD and AL in patients with cataracts in South Korea and Israel [12,34] . It is suggested that female patients with a shallow ACD may be more likely to develop acute primary angle-closure glaucoma than male patients based on cataract impacts.…”
Section: Ocular Biometric Characteristics Of Ethnic Groupssupporting
confidence: 87%
“…Therefore, identifying these differences in ocular biometric parameters is useful for assessing the status of associated ocular diseases and guiding surgical and postoperative care. Relevant studies have been conducted in countries such as the United States, Spain, South Korea, and Bosnia and Herzegovina [9][10][11][12][13] ; however, most of them are limited to a single ethnic group in a single region. Owing to the differences in measuring instruments and patient inclusion criteria, it is difficult to compare ocular biometric parameters between ethnic groups.…”
Section: •Clinical Research•mentioning
confidence: 99%
“…Previous studies with correlation analyses showed significant positive correlations between AL and WTW, [13][14][15]17,18,22,25,[28][29][30] and between AL and ACD. [13][14][15]17,18,[21][22][23][24][25][26][27][28][29][30][31]33,36,37 However, Wei et al 38 reported that there is no linear increasing relationship between AL and WTW, with WTW reaching its maximum at ALs of 24.5 to 26 mm and gradually decreasing. Therefore, the present result on the association between AL and WTW may not necessarily apply in all cases.…”
Section: Discussionmentioning
confidence: 85%
“…The relationship between AL and LT was discussed in Jivrajka et al 33 (R 2 = 0.0321), which made a similar report. Previous studies with correlation analyses pointed out several significant negative correlations between the two, 13,14,16,17,22,27,32,33,36,37 suggesting that LT becomes thinner as AL increases. However, Meng et al 39 linear decreasing relationship between AL and LT.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation